Mediation Essentials - International Finance Corporation (Washington, DC, 2017)
Mediation is one of the most frequently used alternative dispute resolution processes worldwide. Mediation provides faster, cheaper, and better solutions than a traditional court decision can. Benefits are important for individuals as well as for disputing businesses from the private sector and for public sector institutions. Understanding the principles, process, and skills of mediation is essential for anyone whose professional role involves managing disputes of any kind. Mediation Essentials comprises five chapters as follows: 1) Chapter 1 is about How to Manage and Control Disputes and Alternative Dispute Resolution; Chapter 2 describes on How to Make the Most of Mediation; Chapter 3 discusses on How Professional Advisors Can Add Value to Mediation; Chapter 4 explains on How to Use Guiding Principles and Ethics to Ensure the Integrity of Mediation; and Chapter 5 concludes with How to Draft Contractual Documents for Mediation.